Clinical and morphological features of bladder cancer course in HPV-infected patients - A. A. Pulatova; S. N. Dimitriadi; D. S. Kutilin; T. A. Zykova; E. M. Frantsiyants; E. A. Shevyakova; V. K. Hwan; S. I. Goncharov (Южно-Российский онкологический журнал)
Purpose of the study. To study the histological type, grade of tumor differentiation in patients with primary and recurrent clinically non-muscle-invasive bladder cancer (NMIBC) with highly carcinogenic human papillomavirus (HPV) infection.Patients and methods. Formalin-fixed and paraffin-embedded bladder tumor tissue samples have been studied in 159 patients who underwent transurethral resection (TUR) of the bladder, for the presence of HPV DNA. To detect, quantify and differentiate DNA of HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68 genotypes in the samples, the AmpliSense® HPV HRC genotype-titer-FL was used. The result of the study was taken into account when the amount of DNA of the β-globin gene was at least 1000 copies per reaction. In order to statistically analyze our data we used the Fisher exact test and also calculated the odds ratio (OR) and 95 % CI.Results. According to the results of the study, out of 159 patients, high-risk HPV DNA was detected in the tumor tissue in 59 (37.1 %), of which HPV type 16 was found in 52 patients (89.4 %), HPV 18 was detected in 4 patients type (6.7 %) and type 35 in 3 (5.08 %). In a morphological study of the tissues of HPV-positive patients, the grade of tumor differentiation was G2 in 18 cases (30.5 %), G3 in 37 blocks, and G1 was detected only in 4 cases (6.7 %). In the presence of HPV, the chance of detecting a stage G3 tumor increases by 4.3 times. According to the received data, we can assume that there is a close relationship between detection in HPV patients of high-risk genotypes with moderately differentiated and low-differentiated forms of bladder cancer.Conclusion. this study may indicate that HPV infection affects the grade of tumor differentiation, and this, in turn, may allow the use of the HPV test to assess the nature of the development of relapse and/or progression of the disease.